Description of Train Noise Intensity and Subjective Complaints of Residents of RT.02 RW.02, Gunung Pangilun Village, North Padang District, Padang City - Nofrianti, Aderia; Haryani, Sesmeri (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
Settlements along the railroad track will be subject to high noise exposure from train activity. Healthy settlement is a permanent residence, which functions as a place to live, rest, relax and protect from environmental influences. One environmental effect is the presence of noise which can result in subjective complaints that can cause other disturbances. This study aims to determine the intensity of train noise and subjective complaints of residents of RT. 02.02.02. Gunung pangilun sub-district, Padang Utara, Padang City in 2018. The design of this research is descriptive quantitative. The population in this study was taken from the residents of Gunung Pangilun Village who live in the suburbs of the railroad tracks, namely RT. 02 RW.0 2 with 116 residents. Based on the results of noise intensity measurements it is known that within 5 meters of the railroad has a noise intensity of 95 db (A), a distance of 10 meters has a noise intensity of 84 db (A), and a distance of 15 meters has a noise intensity of 73 db (A) exceeding the level the predetermined noise is 55 db (A). While within 20 meters has a noise intensity of 54 db (A). for subjective complaints, the results obtained that more than half of the residents experienced low subjective complaints, namely 28 residents (51.9%) while 26 residents (48.1%) experienced high subjective complaints. To reduce this, people are advised to put rubber dampening on the doors and windows so that the noise that enters the house is reduced and then planting trees such as banyan trees to reduce noise intensity